Higher Fluorosis Severity Makes Enamel Less Resistant to Demineralization (2016)
Fluorotic teeth could either be more resistant or more susceptible to the caries process than sound ones due to their higher enamel fluoride concentration and higher porosity (subsurface hypomineralization), respectively; however, there is no consensus on this subject. In this study, a total of 49 human unerupted third molars presenting Thylstrup and Fejerskov (TF) fluorosis scores 0–4 were used. Two enamel slabs were obtained from each tooth. The rest of the tooth crown was powdered, and the enamel was separated from the dentine. In purified powdered enamel, the calcium (Ca), inorganic phosphate (P i ), and fluoride (F) concentrations were determined. The F concentration gradient throughout the enamel and in the enamel, volume was determined in one slab. The other enamel slab was isolated with acid-resistant varnish, subjecting the exposed enamel surface half to a pH-cycling model to evaluate its demineralization resistance and to calculate the demineralization area. The nonexposed surface was used to determine the natural hypomin eralization area found in fluorotic enamel and normalize the demineralization data. The hypomineralization and demineralization areas were assessed by cross-sectional microhardness. For statistical analyses, the data for TF1 and 2, and for TF3 and 4 were pooled. Concentrations of powered enamel Ca and Pi were not significantly different (p > 0.05) among groups TF0, TF1–2 and TF3–4, but a higher F concentration was found in fluorotic enamel (p < 0.05). Highly fluorotic teeth (TF3–4) presented a greater hypomineralization subsurface area and demonstrated lower demineralization resistance than sound enamel (p < 0.05). The findings suggest that a higher severity of fluorosis makes enamel less resistant to the caries process due to its greater subsurface mineral area exposed to demineralization and deeper acid diffusion through the enamel.